THE ALGORITHM FOR THE TREATMENT OF PATIENTS WITH TREATMENT-RESISTANT HYPERTENSION AT THE OUTPATIENT STAGE - O. S. Kulbachuk; E. V. Sid; O. V. Soloviov; A. V. Piskun (Сучасні медичні технології)
Every year in the world, arterial hypertension is the cause of death in about 9 million cases. Blood pressure control in patients has not yet reached the appropriate level, and the percentage of resistant arterial hypertension remains high. According to the definition of the American Heart Association, those patients whose condition requires taking four or more drugs to control blood pressure should be considered resistant to treatment. It should be understood that uncontrolled hypertension is not synonymous with RAH. The presence of RAH significantly increases the risk of cardiovascular complications, contributes to serious damage to target organs. Preliminary diagnosis of RAH definitely requires the exclusion of secondary hypertension, which is a rather heterogeneous group of diseases that is poorly recognized.